Cardiovascular Health Literacy in Nepal: Increasing awareness of cardiovascular diseases is important but inadequate - Vaidya, Abhinav; Karki, Dambar Bahadur; Krettek, Alexandra (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Cardiovascular Health Literacy in Nepal: Increasing awareness of cardiovascular diseases is important but inadequate